Political transition and novelistic production : blck female writing in South Africa from 1998 to 2011 - (:unkn) unknown (My University, 2017)
The South African political transition from a repressive system to a democratic one opened new spaces to a marginalized part of the population among whom the black woman to express themselves, such as the Truth and Reconciliation hearings. This black feminine voice, made free by the political transition is reflected through the development of a literary female production. It gave way to the emergence of new novelistic forms, analysed in our study through ten novels written by eight different female writers between 1998 and 2011: S. Magona, K.L. Molope, K. Matlwa, A.N. Sithebe, A. Makholwa, H.J. Gololai, Z. Wanner and C. Jele. In a first part, we analyse the way these authors rewrite the novel during the transitional period, moving away from a realistic writing, deeply involved in politics and largely used during the apartheid era, towards a more intimate way of writing which reflect the traumas of a national past haunting the present. Then, we examine in three parts how the writers emerging during the post-transitional period explore new genres, rarely used by black South African women until then, namely the Bildungsroman, detective fiction and chick lit, which reflect their fears in the new South Africa. These authors rewrite these European genres, among which popular ones, through a new feminine perspective, thus innovating the themes they deal with and creating a literature made of mixtures. The European novel becomes a subversive tool to criticise a patriarchal and Europeanised society, which, according to these authors, should not deny the past in order to solve the new challenges coming.
Keywords: African Research